VII Symposium on Application of Noise and Vibration in Diagnostics of Machinery - GADULSKI, Janusz; CZARNECKI, Stefan (Archives of Acoustics, 1981)
The universally occurring acoustic phenomena which accompany the operation of machinery and technological equipment permit wide applications of acoustic signals in computer science and diagnostics. Application of this potential in practice requires development and sophistication of measurement methods, and particularly seeking qualitatively and quantitatively correct estimation of vibration and noise of given machinery. These problems were discussed at the VII Symposium on Application of Noise and Vibration in Diagnostics of Machinery. As previous Symposia it was organized by Institute of Motor Transport of Silesian Technical University on January 11-16, 1981 at Wisla–Malinka. The papers delivered at the Symposium continued the problems discussed at previous conferences. Prof. Dr. Ludwik MULLER was the Scientific Chairman of the Symposium. The Symposium was concluded with a panel session chaired by Prof. Dr. Stefan CZARNECKI of Institute of Fundamental Technological Research, Polish Academy of Sciences, Warsaw.